Markers of Oxidative Stress in Obstetrics and Gynaecology-A Systematic Literature Review - Michalina Anna Drejza; Katarzyna Rylewicz; Ewa Majcherek; Katarzyna Gross-Tyrkin; Małgorzata Mizgier; Katarzyna Plagens-Rotman; Małgorzata Wójcik; Katarzyna Panecka-Mysza; Magdalena Pisarska-Krawczyk; Witold Kędzia; Grażyna Jarząbek-Bielecka (MDPI AG, 2022)
Oxidative stress has been implicated in many diseases, including reproductive and pregnancy disorders, from subfertility to maternal vascular disease or preterm labour. There is, however, discrepancy within the standardized markers of oxidative stress in obstetrics and gynaecology in clinical studies. This review aims to present the scope of markers used between 2012 and 2022 to describe oxidative stress with regard to reproduction, pregnancy, and pregnancy-related issues. Despite the abundance of evidence, there is no consensus on the set of standardised markers of oxidative stress which poses a challenge to achieve universal consensus in order to appropriately triangulate the results.